PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA e - COMMERCE SHOPEE: STUDI PADA MAHASISWA PROGRAM STUDI MANAJEMEN UNIVERSITAS PEMBANGUNAN PANCA BUDI - Hidayati Purnama Lubis; Firdiya Amiyananda (LP2M Universitas Bina Bangsa, 2024)
The presence of internet technology, makes our lifestyle change including shopping patterns. The application of information communication technology that can support the sales system is the emergence of e-commerce. E-commerce is sales made through electronic media. The existence of e-commerce creates an electronic market that connects sellers and buyers which is often known as a marketplace. Marketplace owners facilitate a means for business actors to market their products to the general public and there is a communication space between sellers and buyers to make transactions. The purpose of this study is to determine whether product quality and promotions affect the purchasing decisions of students of the class of 2020 through shopee e-commerce. The results showed that product quality and promotion influenced 29.5% of students' purchasing decisions on the shopee e-commerce platform, while 70.5% were influenced by other variables that were not studied